Model Pembelajaran IPA Berbasis Kecerdasan Spiritual di Sekolah Dasar pada Materi Evolusi Darwin - Anggraeni Marshinta Sulistyani (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2017)
Learning model is a planning or a pattern used as guidance in planning learning in the class or learning in tutorials and to define devices learning belong books, movie, computer, curriculum, and others. Science is a collection of knowledge composed in systematic, and the use of in general limited to symptoms the worlds. One studying in science is the evolution of, namely a change in living things or species also gradually going down. In science learning need to associated with intelligence spiritual to avoid possible misuse of religion and trust against the lord. Because it was necessary the development science learning model based intelligence spiritual in primary school to the matter darwinian evolution with use the model integration. Learning model is in accordance with the 2013 curriculum to teach a material through themes or thematic. The integration of science teaching models they are based on spiritual intelligence. For that, science subjects can be integrated with other subjects that support spiritual intelligence bases such as Islamic Education and Citizenship Education. The integration created a model of intergrated. The development model of science learning based spiritual intelligence in elementary school on a matter of Darwinian evolution has an advantage among other students feel happy with the relationship and the interrelationships between various fields of study, broaden horizons and appreciation of teachers, if it can be implemented well, it can be used as learning models are ideal in the school environment "integrated day", leads people to have a vision, always feel the presence of God, directing people to always dhikr and pray, directing people to always improve the quality of patient, leads people to tend to the kindness, empathy, high-minded, as well as happy serve.